Weekly Paclitaxel given concurrently with Durvalumab has a favorable safety profile in triple-negative metastatic breast cancer - Hazem Ghebeh (Nature Portfolio, 2021)
Abstract Therapeutic anti-PD-L1 antibodies are safe as a monotherapy, albeit with minimal efficacy in triple-negative breast cancer (TNBC). This trial aimed to test the safety and efficacy of Durvalumab and Paclitaxel in metastatic TNBC. In this open-label, one-arm trial, five cycles of weekly paclitaxel were delivered intravenously (IV) concurrent with Durvalumab that was given IV every 2 weeks. The combination was preceded by one cycle of paclitaxel alone, for immunological priming, followed by Durvalumab solo until disease progression or unacceptable toxicity. Between 2017 and 2019, 14 patients received at least one cycle of the combination therapy. The therapy was safe with no-dose limiting toxicity, except one case of skin lesions. Adverse events (AEs) were reported in 71% of patients, and there was no death due to the combination therapy. Regardless of grade, the most common AEs were headache and peripheral neuropathy, as each happened in four patients (29%), followed by fatigue and skin rash in three patients (21%) each. Grade 3/4 AEs were experienced by three patients (21%), with the most common being headache and anemia, which happened in two patients (14%). The confirmed objective response rate (ORR) was observed in five patients with a median duration of 10.0 months. Median Progression-free survival (PFS) and overall survival (OS) were 5 and 20.7 months, respectively. The combination of Durvalumab and Paclitaxel is safe, leaving room for additional agents. This is the first report on the combination of Durvalumab and Paclitaxel in the treatment of TNBC (NCT02628132).